Mucosal Administration of Flagellin Induces Innate Immunity in the Mouse Lung - Honko, Anna N. (American Society for Microbiology, 2004)
Nonsurgical intratracheal instillation of 1 μg of purified, recombinant flagellin in several strains of mice stimulated a transient innate immune response in the lung characterized by the infiltration of neutrophils and the rapid production of tumor necrosis factor alpha, interleukin 6, granulocyte colony-stimulating factor, and the chemokines keratinocyte-derived chemokine, MIP1α, and MIP-2.